The role of genomic profiling in adolescents and young adults (AYAs) with advanced cancer participating in phase I clinical trials. (May 2018) - McVeigh, Terri Patricia; Sundar, Raghav; Diamantis, Nikolaos; Kaye, Stan B.; Banerji, Udai; Lopez, Juanita S.; de Bono, Johann; van der Graaf, Winette T.A.; George, Angela J.
Abstract: Introduction: Adolescents and young adults (AYAs) diagnosed with cancer between ages 15–39 years may harbour germline variants associated with cancer predisposition. Such variants represent putative therapeutic targets, as may somatic variants in the tumour. Germline and tumour molecular profiling is increasingly utilised to facilitate personalisation of cancer treatment in such individuals. Aim: Considering AYAs with advanced solid tumours managed in a specialist drug development unit (DDU), the aims of this study were to investigate the use and impact of: 1. Germline genetic assessment. 2. Tumour molecular profiling. Methods: AYAs treated in the DDU at the Royal Marsden Hospital between 2002 and 2016 were identified from departmental databases. Data regarding clinicopathological features, clinical assessments and germline and tumour genetic testing were retrieved by chart review. Results: The study cohort included 219 AYAs. Common cancer types included sarcoma (41, 19%); cervical (27, 12%); breast (25, 11%); ovarian (23, 11%) and colorectal (21, 10%) cancers. Germline testing was undertaken in 34 (16%) patients, 22 of whom carried a pathogenic variant. Using current testing criteria, an additional 32 (15%) would be eligible for germline testing based on their personal history of cancer alone. Tumour testing was undertaken in 46 (21%) individuals. Somatic mutations were commonly identified in TP53 13 (28%); PIK3CA (8, 18%); KRAS (4, 9%) and MET 5 (11%). Discussion: A significant proportion of AYAs with advanced cancer have targetable somatic or germline mutations. Consideration of familial risk factors and inclusion of germline testing wherever appropriate can complement tumour testing to optimise patient management and inform management of at-risk relatives. Highlights: Adolescents/young adults with cancer may have a germline cancer predisposition. Some AYAs should have germline genetic testing, even in absence of family history. Documentation of family history of AYAs with cancer is unsatisfactory. Tumour-based genetic testing may identify clinically targetable mutations. Larger multi-gene panels increase uncertainty as well as diagnostic yield.